270 H1N1 Pandemic: Comparison of the Clinic Presentation between Canada and France in Critically Ill Children. (October 2012) - Fléchelles, O; Brissaud, O; Fowler, R; Jouvet, P
Abstract : Background and Aims: The 2009 H1N1 pandemic (pH1N1) induced a large number of admissions of children in pediatric intensive care units (PICU). The objective of this study was to compare the severity of the 2 nd wave of pH1N1 between France and Canada. Methods: All patients admitted to a pediatric intensive care unit (PICU) in Canada (PICU=16) and France (PICU=25) between October 1 st 2009 and January 31 st 2010, with a documented H1N1 infection were included. Results: 160 children in Canada (prevalence = 2.6/100 000 children) and 125 children in France (prevalence = 1.6/100, 000), were hospitalized in SIP. pH1N1 incidence curve was different in the two countries (figure ). pH1N1 acute respiratory failure was more severe in France, with a lower incidence, and a low vaccination rate (Table ). Conclusion: pH1N1 2 nd wave was different between Canada and France. The low vaccination rate in France is associated with an increase in severity but non in incidence.